FUNGSI TARI SELODANG MAYANG DI ISTANA AMANTUBILLAH KABUPATEN MEMPAWAH - Saputri, Suri; Ismunandar, Ismunandar; Tindarika, Regaria (Universitas Tanjungpura, 2023)
This research discusses the function of the Selodang Mayang dance which is in the Amantubillah Palace environment with the meaning of having to hold the marwah of customs to maintain and maintain cultural preservation, the problem found in this research is that this dance can only be performed in the Amantubillah palace not just anyone can dance and witness the Selodang Mayang dance, The purpose of this study is to describe the function of the Selodang Mayang Dance at the Amantubillah Palace, Mempawah Regency. This study used a descriptive method with a qualitative research form using an anthropological approach. The research location was carried out at the Amantubillah Palace, East Mempawah District, Mempawah Regency. The research data sources are Raja Mardan, Deki Prasetya Ardiansyah, and Roby Suhendra. Data collection uses observation, interviews, and documentation. Data analysis techniques using interactive models. Results and discussion a) Selodang Mayang dance at the Amantubillah Palace, Mempawah Regency, b) The function of the Selodang Mayang dance at the Amantubillah Palace, Mempawah Regency as entertainment, c) The function of the Selodang Mayang dance at the Amantubillah Palace, Mempawah Regency as entertainment, d) The function of the Selodang Mayang dance at the Palace Amantubillah Mempawah Regency as a Ritual, e) The function of the Selodang Mayang Dance at the Amantubillah Palace, Mempawah Regency as an educational medium, f) The function of the Selodang Mayang dance at the Amantubillah Palace, Mempawah Regency as a social function.